Pós-colheita de frutos de morangueiro submetidos a aplicação de hidroxietilcelulose e própolis aquoso - Minarelli, Philipp Herbst [UNESP]; Daiuto, Érica Regina [UNESP]; Vieites, Rogério Lopes [UNESP] (My University, 2014)
The strawberry is a nutritious fruit of great commercial value, consumed in fresh form and very used in theelaboration of several desserts types. However, it is highly perishable presenting short period postharvest. Theaim of this work was to evaluate the quality of strawberries cv. Aroma, covered for edible film ofhydroxetylcelullose and propolis aqueous extract maintained under refrigeration(0±1°C e relative humidity of75±5%).Thetreatmentswere:control(T1-without hydroxetylcelulloseand without propolis), hydroxetylcelullose without propolis (T2), propolis 100% (T3), hydroxetylcelullose and propolis 0,5% (T4), hidroxietilcelulose and propolis 1,0% (T5) and hydroxetylcelullose and propolis 1,5% (T6). The strawberries were evaluated for weight loss, respiratory activity, potential hidrogenionic (pH), acidity tritable (AT), soluble solids (SS) and maturation index (SS/AT). The T5 provided to the strawberries to smallest weigth loss and production of CO 2 . For the other evaluated parameters difference was not observed among the treatments, but some alterations during the experimental period.

O morango é um altamente perecível apresentando curto período pós colheita. O objetivo deste trabalho foiavaliar a qualidade de morangos cv. Aroma, recobertos por filme comestível de hidroxetilcelulose e extratoaquoso de própolis mantidos sob refrigeração (0±1°C e umidade relativa de 75±5%). Os tratamentos foram:controle (T1 - sem hidroxietilcelulose e sem própolis), hidroxietilcelulose sem própolis (T2), própolis 100% (T3),hidroxietilcelulose e própolis 0,5% (T4), hidroxietilcelulose e própolis 1,0% (T5) e hidroxietilcelulose e própolis1,5% (T6). Os morangos foram avaliados quando a perda de massa, atividade respiratória, potencialhidrogeniônico (pH), acidez titulável (AT), sólidos solúveis (SS) e índice de maturação (SS/AT). O T5proporcionou aos morangos a menor perda de massa e produção de CO2.Para os demais parâmetros avaliadosnão foi observada diferença entre os tratamentos, apenas alterações durante o período do experimento.
Postharvest behavior of strawberry of fruits subjected to the application to the hydroxyetilcellulose and aqueous propolis
Keywords: Fragaria ananassa Duch; cv. Aroma; Edible film; Fragaria ananassa Duch; cv. Aroma; Filme comestível